(untitled) (Global Journal of Science Frontier Research, 2023)
Water is the home of fishes which may be fresh, brackish and marine. The present study is entirely based on freshwater fishes. PurbaMedinipur district has the potentiality for large fresh water resources. In this district, Contai is an important vital area because it is also a coastal based zone. Therefore the present study is very significant. Total of 46 native fish species were identified in this Municipality from the period of July 2021 to June 2022. Here total 46 freshwater fish species were observed under the 07 orders and 20 families.